Size effects on residual stress and fatigue crack growth in friction stir welded 2195-T8 aluminium - Part I: Experiments - Ma, Yu E.; Staron, P.; Fischer, T.; Irving, Phil E. (Elsevier Science B.V., Amsterdam., 2011)
Residual stress fields were measured in three different sizes of Compact-Tension (C(T)) and eccentrically loaded single edge notch (ESE(T)) specimens containing transverse or longitudinal welds. The effect of size on residual stress profiles was studied. Fatigue crack growth tests were carried out with cracks growing into or away from the weld line, as well as growing along the weld centre line. Effects of weld residual stresses on fatigue crack growth rates parallel and perpendicular to the friction stir welds were studied. It was found that compressive residual stresses around the sample notch had significant retarding effects on both crack initiation and crack growth rates for cracks growing towards the weld line. Effects of residual stress on crack growth rates declined with increasing crack length. When cracks grew parallel to the weld line in C(T) samples the crack growth rate was around 20% lower than in parent material.
Keywords: Friction stir weld; Residual stress; Sample size effect; Crack closure; Fatigue crack growth